MONITORING OF CMV INFECTION IN KIDNEY TRANSPLANT RECIPIENTS - Zhivka Stoykova; Liliya Ivanova; Valentin Ikonomov; Iliana Teodorova; TatinaTodorova (Peytchinski Publishing, 2017)
Human cytomegalovirus is a ubiquitous herpesvirus that establishes lifelong latency after primary infection, but can cause life-threatening disease in immunosuppressed patients. CMV invasive disease leads to significant morbidity and mortality following kidney transplantation. We tested 2 groups of patients - Group A included 20 potential kidney recipients and 29 potential donors investigated by ELISA and Group B included 53 adult kidney transplant recipients all of them tested in ELISA and 24 of them tested in QRT-PCR for CMV-DNA from plasma samples. In group A 16 (80%) of 20 potential kidney recipients were anti-CMV IgG positive and 4 (20%) were anti-CMV IgG negative. Twenty eight of 29 potential donors were found seropositive, and only one was not infected. In group B overall 119 ELISA tests for specific anti-CMV antibodies were performed. Anti-CMV IgM negative was 68 (57%) of the tested samples, twelve (10%) showed anti-CMV IgM equivocal results and 39 samples (33%) were with anti-CMV IgM positive. Seven of them (13,2%) showed repeatedly anti CMV IgM positive results. All 119 (100%) displayed аnti-CMV IgG positive results. Overall 41 PCR analyses from plasma samples of 24 kidney transplant recipients (group B) were performed. CMV-DNA replication was detected in 5 plasma samples obtained from 3 patients (12.5%) at a different time - from 20 days till almost 8 years after the transplantation. Despite the high seroprevalence to CMV 20% of the potential recipients were at high risk of primary infection when receiving a kidney from a seropositive donor. Positive serological results during the regular post-transplantation monitoring complemented with or without clinical data are indicative and require further QRT-PCR analysis.